USING SENTINEL-2 IMAGE FOR MANGROVE HEALTH ANALYSIS IN BAKAU KECIL VILLAGE, MEMPAWAH DISTRICT, WEST KALIMANTAN - Ajun Purwanto; Paiman Paiman (Universitas Sebelas Maret (UNS), 2024)
This study aims to determine 1) The index of mangrove plant vegetation density, and 2) the state of the mangrove plants in the village of Bakau Kecil. Transforming the NDVI was the method employed in this study. The canopy density model can be applied using NDVI. The degree of vegetation canopy density was correlated with the intensity of greenness. The outcomes demonstrated that NDVI values ranged from -1 to 0.32, indicating sparse vegetation density, 0.33 to 0.42, indicating medium density values, and 0.43 to 1, indicating dense density values. One can categorize the condition of the mangrove vegetation based on the NDVI index value, which is shown above. Based on a vegetation index value of 0.43 - 1, which indicates very good health, mangrove vegetation can be considered to be in excellent condition. The mangrove vegetation is in good health (vegetation value 0.33-0.42, Moderate), and the vegetation is in poor health (vegetation value -1-0.32, Rare), according to the vegetation index. Mangrove health is very good, with a pixel area percentage of 68.88 percent; good health has a pixel area percentage of 23.98 percent; and poor health has a pixel area percentage of 7.14 percent.